Improving education outcomes by linking payments to results: an assessment of disbursement-linked indicators in five results-based approaches - Sarah Holzapfel; Heiner Janus (Deutsches Institut für Entwicklungspolitik (DIE), 2015)
In results-based approaches, funding is linked to pre-agreed results that are defined in the form of indicators. Disbursements only take place once progress in the indicators has been verified. This places high requirements on the quality of indicators used. Different development actors have started implementing results-based approaches, yet little attention has been paid to potential advantages and disadvantages of the specific indicators that are used. The paper addresses this gap by first conceptualising a typology of indicators and devising criteria for assessing the quality of indicators. The typology and criteria are then applied to five results-based pilot programmes in the education sector in developing countries (Ethiopia, Rwanda, Sri Lanka, Tanzania). A comparison of the indicators used across these programmes provides insights into how indicators for results-based approaches can be selected in a more informed manner in the future. Key words: results-based approaches, results-based aid, development cooperation, disbursement-linked indicators, education
Keywords: 330; Entwicklungsfinanzierung und öffentliche Finanzen; Wirksamkeit und Evaluierung